Carbon quantum dot corrosion inhibitor as well as preparation method and application thereof

The preparation of carbon quantum pit corrosion inhibitors through brewing and brewing yellow water has solved the problem of low resource utilization in brewing wastewater treatment in the liquor industry, achieved efficient resource utilization and environmentally friendly corrosion inhibition effects, and provided a solution to the new green corrosion inhibitor. plan.

CN119265569APending Publication Date: 2025-01-07WULIANGYE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411371400.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The utilization rate of organic resources in the liquor industry's brewing wastewater treatment is low, resulting in resource waste and environmental pollution. The traditional treatment model cannot meet the development needs of modern enterprises.

Method used

Using the brewing rice ginger as raw material, carbon quantum point corrosion inhibitor is prepared through reduced pressure distillation and hydrothermal reaction, and nitrogen is used to dopate nitrogen, which realizes the resource utilization of brewing rice ginger and shows good relaxation in the acidic solution. corrosion performance.

Benefits of technology

The resource utilization of brewing yellow water has been realized, the generation cost of carbon quantum pit corrosion inhibitors has been reduced, new ideas have been provided, the preparation process has been simplified, and the corrosion inhibition performance has been efficient, especially in strong acid media. Excellent performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265569A_ABST
    Figure CN119265569A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon quantum dot corrosion inhibitor as well as a preparation method and application thereof, and belongs to the technical field of resource utilization. The invention provides a carbon quantum dot corrosion inhibitor as well as a preparation method and application thereof in order to realize resource utilization of wine-making yellow water, and the preparation method comprises the following steps: performing reduced pressure distillation on the wine-making yellow water, and drying to obtain a yellow water organic matter; mixing the obtained yellow water organic matter and water according to the mass volume ratio of 1g: 1-5mL, performing hydrothermal reaction, centrifuging, collecting supernate, dialyzing, and performing freeze drying, thereby obtaining the yellow water organic matter. In addition, before the hydrothermal reaction, a nitrogen source can be added for nitrogen doping. The carbon quantum dot corrosion inhibitor with good corrosion inhibition performance is directly prepared by taking the wine-making yellow water as a raw material through a hydrothermal method, in addition, the performance of the corrosion inhibitor can be further improved by adding a nitrogen source, and a new thought is provided for resource utilization of the wine-making yellow water and preparation of the carbon quantum dot corrosion inhibitor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of resource utilization, and specifically relates to a carbon quantum dot corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] As a unique distilled liquor variety in my country, liquor has a development history of more than 3,000 years. According to incomplete statistics, 15 to 20 tons of brewing wastewater will be produced for every ton of liquor produced during the liquor production process. Therefore, brewing wastewater has become an urgent problem that needs to be solved urgently to restrict the green and high-quality development of the liquor industry. With the development and improvement of water treatment technology, large-scale liquor companies in my country have their own unique sewage treatment projects with stable processes, and the treated water quality meets the requirements of national and local emission standards. However, the low utilization rate of organic resources in wastewater not only causes waste of resources, but also leads to the production of harmful gases and greenhouse gas emissions due to aerobic and anaerobic treatment. In addition, the resulting sludge further increases the cost of enterprise treatment and disposal. With the continuous expansion of the scale of liquor enterprises, the traditional brewing wastewater treatment model can no longer meet the development needs of modern enterprises. In response to the problems of large water consumption and pollution discharge in the liquor brewing industry, the state has issued standards such as "Clean Production Standard Liquor Manufacturing (HJ / T 402-2007)" and "Fermented Alcohol and Liquor Industry Water Pollutant Emission Standard (GB27631-2011)" to control pollution, save energy and reduce emissions. The resource utilization of sewage and the extraction of other resources and energy from sewage are of great significance to alleviating the contradiction between supply and demand, reducing water pollution, ensuring water ecological security, increasing water resources supply, and optimizing water supply structure. Liquor brewing uses grain as raw materials, and the wastewater produced is rich in various organic matter and less harmful substances, which has reuse value. Therefore, research on governance methods that can fully recycle resources while taking into account environmental, social and economic benefits will surely become the main direction of wastewater treatment in the future liquor industry.

[0003] Corrosion inhibitor is a chemical substance or a mixture of several chemical substances that can prevent or slow down corrosion when it exists in the environment (medium) in an appropriate concentration and form. Generally speaking, corrosion inhibitors refer to substances that are used to protect metal surfaces. Adding trace or small amounts of such chemicals can significantly reduce the corrosion rate of metal materials in the medium to zero. At the same time, the original physical and mechanical properties of the metal materials can be kept unchanged. The rational use of corrosion inhibitors is an effective way to prevent metals and their alloys from corroding in environmental media. Corrosion inhibitor technology has become one of the most widely used methods in anti-corrosion technology due to its good effects and high economic benefits. Especially in the production and processing of petroleum products, chemical cleaning, atmospheric environment, industrial water, machinery, instrument manufacturing and petrochemical production processes, corrosion inhibition technology has become one of the main means of corrosion prevention. As people pay more and more attention to environmental pollution and human health, finding a new "green corrosion inhibitor" with high corrosion inhibition rate, environmental protection, good water solubility and low price has become a hot spot in the current research and development of corrosion inhibitors.

[0004] Carbon dots, also known as carbon quantum dots or carbon nanodots, are a type of zero-dimensional carbon nanomaterials with significant fluorescent properties. They are composed of ultrafine, dispersed, quasi-spherical carbon nanoparticles with a size of less than 10nm. Carbon dots have many advantages such as excellent optical properties, good water solubility, low toxicity, environmental friendliness, wide source of raw materials, low cost, good biocompatibility, etc., and have good application prospects in many fields such as medical imaging technology, environmental monitoring, chemical analysis, catalyst preparation, energy development, etc. Carbon dots have received widespread attention in the field of corrosion protection, and studies have shown that carbon dot corrosion inhibitors can play a good corrosion inhibition role on metals.

[0005] As an important component of brewing wastewater, brewing yellow water comes from the brown-yellow viscous slurry that seeps from the mash to the bottom of the cellar during the solid-state fermentation of liquor. It is a typical high-concentration organic wastewater. At the same time, yellow water is rich in organic matter such as sugars, acids, esters, and proteins, and has the potential for resource utilization. Therefore, exploring the use of rich organic matter in brewing yellow water as raw materials to prepare carbon dot corrosion inhibitors and realize the resource utilization of organic matter in brewing yellow water will not only help reduce resource waste, but also reduce the pollution to the environment during the discharge process. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a carbon quantum dot corrosion inhibitor and a preparation method and application thereof. The present invention uses brewing yellow water as raw material to prepare the carbon quantum dot corrosion inhibitor, thereby realizing the resource utilization of brewing yellow water, and the prepared carbon quantum dot corrosion inhibitor has good corrosion inhibition performance.

[0007] To achieve the above object, the present invention first provides a method for preparing a carbon quantum dot corrosion inhibitor, which comprises the following steps:

[0008] A. Yellow water from winemaking is subjected to vacuum distillation (the temperature is controlled not to exceed 50°C during vacuum distillation) and dried to obtain yellow water organic matter;

[0009] B. The yellow water organic matter obtained in step A and water are mixed at a mass volume ratio of 1 g: 1-5 mL, and a hydrothermal reaction is carried out. After the reaction is completed, the mixture is centrifuged, the supernatant is collected for dialysis, and finally freeze-dried to obtain a carbon quantum dot corrosion inhibitor.

[0010] Wherein, in the above preparation method, in step B, a nitrogen source is also added before the hydrothermal reaction.

[0011] Wherein, in the above preparation method, in step B, the amount of the nitrogen source added is controlled to control the molar mass ratio of the nitrogen content in the nitrogen source to the organic matter in the yellow water to be 0.1-0.5:100.

[0012] Wherein, in the above preparation method, in step B, the nitrogen source is at least one of ammonia water, urea, ethylenediamine, triethanolamine or thiourea.

[0013] Preferably, in the above preparation method, in step B, the nitrogen source is triethanolamine.

[0014] Among them, in the above preparation method, in step A, before the reduced pressure distillation, the suspended matter in the brewing yellow water is first removed by standing and filtering.

[0015] Wherein, in the above preparation method, in step A, the drying is: low-temperature drying or freeze-drying at a temperature not exceeding 50°C.

[0016] Wherein, in the above preparation method, in step B, the temperature of the hydrothermal reaction is 180-300°C.

[0017] Wherein, in the above preparation method, in step B, the time of the hydrothermal reaction is 4 to 12 hours.

[0018] Wherein, in the above preparation method, in step B, the centrifugal speed is 3000-10000 r / min.

[0019] Wherein, in the above preparation method, in step B, the centrifugation time is 20 to 40 minutes.

[0020] Wherein, in the above preparation method, in step B, the dialysis is: using a dialysis bag with a cutoff of 1000 to 3500 Da, and dialysis for 1 to 3 days.

[0021] The present invention also provides a carbon quantum dot corrosion inhibitor, which is prepared by using the above-mentioned method for preparing the carbon quantum dot corrosion inhibitor.

[0022] The present invention also provides the use of the carbon quantum dot corrosion inhibitor in slowing down the corrosion of metal substrates in an acidic solution environment.

[0023] Wherein, in the above application, the acidic solution is an aqueous solution of sulfuric acid, hydrochloric acid or nitric acid.

[0024] Wherein, in the above application, the H + The concentration is 0.1~6.0mol / L.

[0025] Wherein, in the above application, the added amount of the carbon quantum dot corrosion inhibitor is 5 to 100 mg / L acidic solution.

[0026] Beneficial effects of the present invention:

[0027] The present invention uses brewing yellow water as a raw material and directly prepares a carbon quantum dot corrosion inhibitor by a hydrothermal method. In addition, a nitrogen source can be added to prepare a nitrogen-doped carbon quantum dot corrosion inhibitor, thereby realizing the resource utilization of brewing yellow water. The prepared carbon quantum dot corrosion inhibitor and nitrogen-doped carbon quantum dot corrosion inhibitor have good corrosion inhibition performance, especially when triethanolamine is used as the nitrogen source, the corrosion inhibition efficiency can reach 86% and 88% or more, respectively.

[0028] By using the carbon quantum dot corrosion inhibitor prepared by the present invention, after the carbon steel is corroded in a strong acid medium, the surface of the carbon steel is relatively smooth without quality defects such as black spots and darkening. The carbon quantum dot corrosion inhibitor of the present invention has wide promotion and application value.

[0029] The present invention realizes the resource utilization of yellow water from brewing and also provides a new idea for the preparation of carbon quantum dot corrosion inhibitors, which is beneficial to reducing the production cost of carbon quantum dot corrosion inhibitors. At the same time, the preparation method of the present invention is simple, easy to industrialize, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the infrared spectrum of carbon quantum dot corrosion inhibitor A.

[0031] Figure 2 This is the elemental analysis result diagram of carbon quantum dot corrosion inhibitors A, B, C and D; among them, a is carbon quantum dot corrosion inhibitor A, b is carbon quantum dot corrosion inhibitor B, c is carbon quantum dot corrosion inhibitor D, and d is carbon quantum dot corrosion inhibitor D.

[0032] Figure 3 The potentiodynamic polarization curves of carbon steel electrodes in 1M HCl containing different amounts of carbon quantum dot corrosion inhibitor A at different temperatures; where a is 20°C, b is 30°C, c is 40°C, and d is 50°C.

[0033] Figure 4These are the three-dimensional contour diagrams of the uncorroded carbon steel substrate at 20°C and in 1M HCl without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitor A; among them, a is the uncorroded carbon steel substrate, b is the substrate without adding corrosion inhibitor, and c is the substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor A.

[0034] Figure 5 These are scanning electron microscope images of an uncorroded carbon steel substrate at 20°C and in 1M HCl without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitor A; wherein, a is an uncorroded carbon steel substrate, b is a substrate without adding corrosion inhibitor, and c is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor A.

[0035] Figure 6 These are atomic force microscopy images of an uncorroded carbon steel substrate at 20°C and in 1M HCl without adding a corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitor A; wherein, a is an uncorroded carbon steel substrate, b is a substrate without adding a corrosion inhibitor, and c is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor A.

[0036] Figure 7 Potentiodynamic polarization curves of carbon steel electrode in 1M HCl at 20°C without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D respectively.

[0037] Figure 8 These are three-dimensional contour diagrams of an uncorroded carbon steel substrate at 20°C and in 1M HCl without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D respectively; wherein a is an uncorroded carbon steel substrate, b is a substrate without adding corrosion inhibitor, c is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor A, d is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor B, e is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor C, and f is a substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor D.

[0038] Fig. 9 These are scanning electron microscope images of an uncorroded carbon steel substrate at 20°C and in 1M HCl without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D respectively; wherein, a is an uncorroded carbon steel substrate, b is no corrosion inhibitor added, c is adding 100 mg / L carbon quantum dot corrosion inhibitor A, d is adding 100 mg / L carbon quantum dot corrosion inhibitor B, e is adding 100 mg / L carbon quantum dot corrosion inhibitor C, and f is adding 100 mg / L carbon quantum dot corrosion inhibitor D.

[0039] Fig.10These are the atomic force microscope 3D images of the uncorroded carbon steel substrate at 20°C and in 1M HCl without adding corrosion inhibitor and with adding 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D respectively; among them, a is the uncorroded carbon steel substrate, b is the substrate without adding corrosion inhibitor, c is the substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor A, d is the substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor B, e is the substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor C, and f is the substrate with adding 100 mg / L carbon quantum dot corrosion inhibitor D. DETAILED DESCRIPTION

[0040] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the scope of the examples.

[0041] Example 1

[0042] 1. Preparation of Carbon Quantum Dot Corrosion Inhibitor

[0043] (1) The brewing yellow water sample is first allowed to stand for 24 hours to allow large insoluble particles such as rice husks, wheat bran, and broken grain particles in the brewing yellow water to settle naturally. The sample is then filtered under reduced pressure and the filtrate is collected. Water is recovered by distillation under reduced pressure. When there are no water droplets on the wall of the condensation reflux pipe, the distillation is stopped. The sample is then dried at low temperature (low temperature drying or freeze drying at a temperature below 50°C) to obtain a reddish-brown viscous liquid substance, which is recorded as yellow water organic matter and used in the subsequent synthesis study of corrosion inhibitors.

[0044] (2) Weigh 40.00 g of the yellow water organic matter obtained in step (1) and 80.00 mL of deionized water and place them in a polytetrafluoroethylene reactor. Perform a hydrothermal reaction at 180° C. for 12 h. After the reaction, the turbid liquid obtained was centrifuged at 3000 r / min for 30 mins. The supernatant was collected and dialyzed for 3 days using a dialysis bag with a molecular cutoff of 1000 Da. After freeze-drying, the carbon quantum dot corrosion inhibitor A was obtained.

[0045] (3) Weigh 40.00 g of the yellow water organic matter obtained in three portions of step (1), and then add ammonia water, urea, and triethanolamine, respectively, according to the nitrogen content of 0.15 mol (19.83 g of ammonia water, 4.50 g of urea, and 22.38 g of triethanolamine) and 60.00 mL of deionized water in a polytetrafluoroethylene reactor, and hydrothermally react at 180° C. for 12 h. After the reaction, the turbid liquid obtained was centrifuged at 3000 r / min for 30 mins, and the supernatant was collected and dialyzed for 3 days using a dialysis bag with a molecular cutoff of 1000 Da. After freeze-drying, carbon quantum dot corrosion inhibitor B, carbon quantum dot corrosion inhibitor C, and carbon quantum dot corrosion inhibitor D were obtained.

[0046] 1. The carbon quantum dot corrosion inhibitor A obtained in this example was subjected to infrared spectroscopy detection, and the results were as follows: Figure 1 shown.

[0047] from Figure 1 It can be found that the carbon quantum dot corrosion inhibitor A has a peak at 2961 cm -1 There are broad and strong absorption peaks at 2893 and 2718 cm, which are generally attributed to the stretching vibration of OH bonds. -1 The infrared absorption peak at 1591cm is the stretching vibration peak of the CH bond. -1 and 1382cm -1 The absorption peaks at 1358 cm-1 correspond to the stretching vibrations of the C=C bond and the N=N bond, respectively. -1 and 1109cm -1 The peaks at may come from the stretching vibrations of CN bonds and CO, respectively.

[0048] 2. The carbon quantum dot corrosion inhibitors A, B, C, and D obtained in this example were subjected to elemental analysis. The results are as follows: Figure 2 As shown. Figure 2 (a) to (d) are the elemental analysis results of carbon quantum dot corrosion inhibitors A, B, C, and D, respectively.

[0049] from Figure 2 It can be found that the synthetic carbon quantum dot corrosion inhibitor A mainly contains C, H, and O elements, and the carbon quantum dot corrosion inhibitors B, C, and D contain N elements in addition to the three elements contained in the carbon quantum dot corrosion inhibitor A, indicating that the nitrogen doping is successful. The presence of heteroatoms such as O and N can serve as active action sites of the synthesized corrosion inhibitors and interact with the metal surface, thereby giving them potential good corrosion inhibition properties.

[0050] 2. Performance Study of Carbon Quantum Dot Corrosion Inhibitor A

[0051] At different temperatures, a carbon steel electrode was placed in a 1M HCl solution, and different concentrations of the carbon quantum dot corrosion inhibitor A prepared in Example 1 were added to obtain potentiodynamic polarization curves, as shown in FIG. Figure 3 As shown, Figure 3 (a), 3(b), 3(c) and 3(d) are the potentiodynamic polarization curves at 20℃, 30℃, 40℃ and 50℃, respectively.

[0052] from Figure 3 It can be seen that the addition of carbon quantum dot corrosion inhibitor A has no significant effect on the shape of the polarization curve, indicating that the addition of carbon quantum dot corrosion inhibitor A does not change the reaction mechanism of carbon steel in 1M HCl solution. It mainly prevents the corrosion of carbon steel by adsorbing on the surface of carbon steel and occupying the active sites on the surface of carbon steel. Figure 3 It can be seen that after adding the corrosion inhibitor, both the cathode branch and the anode branch of the polarization curve move toward the low current density direction, which indicates that the carbon quantum dot corrosion inhibitor A can simultaneously inhibit the dissolution of carbon steel at the anode and the precipitation of hydrogen at the cathode.

[0053] right Figure 3 The polarization curves in the figure and the corrosion electrochemical parameters obtained by extrapolating the Tafel linear segment are shown in Table 1, where the calculation formula for the corrosion inhibition efficiency (η) is shown in Formula (1-1).

[0054] η=(1-i corr,inh / i corr,0 )×100 % (1-1)

[0055] Where: i corr,inh and i corr,0 are the corrosion current density of carbon steel electrode in the solution with corrosion inhibitor added and in the blank solution, respectively.

[0056] Table 1 Electrochemical parameters of carbon steel electrode in 1M HCl containing different concentrations of carbon quantum dot corrosion inhibitor A

[0057]

[0058]

[0059] It can be seen from Table 1 that the addition of carbon quantum dot corrosion inhibitor A has an effect on the corrosion potential E corr The effect of the corrosion current density i corr The value of is gradually decreasing, indicating that the adsorption of carbon quantum dot corrosion inhibitor A on the carbon steel surface inhibits the corrosion of carbon steel, and the corresponding corrosion inhibition efficiency is also increasing. corrr The value of increases overall, indicating that the acid solution strengthens the corrosion of carbon steel. However, the corrosion inhibition efficiency of carbon quantum dot corrosion inhibitor A on carbon steel does not change significantly with the increase of temperature. When the corrosion inhibitor concentration is 100 mg / L and above, the corrosion inhibition efficiency increases slightly. At 50°C, the corrosion inhibition efficiency can reach up to 96.4%. This shows that carbon quantum dot corrosion inhibitor A has good corrosion inhibition performance on carbon steel in 1M HCl solution.

[0060] 2. Weight loss experiment and surface morphology analysis of carbon steel in 1M HCl solution

[0061] The corrosion rate (v) and corrosion inhibition efficiency (η) of carbon steel in 1M HCl without corrosion inhibitor and with different concentrations of carbon quantum dot corrosion inhibitor A at 20°C were determined by weight loss method. The results are shown in Table 2.

[0062] Table 2 Weight loss data of carbon steel at 20℃ immersed in 1M HCl solution for 4h

[0063]

[0064] Table 2 shows that, relative to the blank solution without adding corrosion inhibitor, as the concentration of carbon quantum dot corrosion inhibitor A increases, the corrosion rate v decreases and the corrosion inhibition efficiency η increases. The corrosion rate of carbon steel in 1M HCl is 1.522 mg·m -2 ·h -1 The corrosion rate of carbon steel in 1M HCl solution with 100 mg / L carbon quantum dot corrosion inhibitor A is 0.200 mg·m -2 ·h -1 The corrosion inhibition efficiency is as high as 86.86%, indicating that carbon quantum dot corrosion inhibitor A significantly inhibits the corrosion of carbon steel in 1M HCl.

[0065] Furthermore, after the experiment, the corrosion morphology of the sample surface was tested using a three-dimensional profiler, scanning electron microscope (SEM) and atomic force microscope (AFM). At 20°C, the three-dimensional profile, SEM and AFM images of the uncorroded carbon steel substrate and the 1M HCl without adding corrosion inhibitor (control group) and adding 100 mg / L carbon quantum dot corrosion inhibitor A (experimental group) were obtained. The results are as follows Figure 4 , Figure 5 , Figure 6 As shown, (a) is the carbon steel substrate, (b) is the control group, and (c) is the experimental group, where Sa is the arithmetic mean height of the surface and Ra is the surface roughness.

[0066] from Figure 4 , Figure 5 , Figure 6 It can be seen that the surface of carbon steel in the control group was severely corroded, while the surface of carbon steel samples in the experimental group was slightly corroded without obvious signs of corrosion, indicating that carbon quantum dot corrosion inhibitor A has a good inhibitory effect on the corrosion of carbon steel in 1M HCl solution.

[0067] 3. Performance Study of Carbon Quantum Dot Corrosion Inhibitors B, C, and D

[0068] 1. At 20°C, a carbon steel electrode was placed in a 1M HCl solution, and 100 mg / L of the carbon quantum dot corrosion inhibitors A, B, C, and D prepared in Example 1 were added to obtain a potentiodynamic polarization curve, as shown in FIG. Figure 7 shown.

[0069] from Figure 7It can be seen that the addition of carbon quantum dot corrosion inhibitors A, B, C, and D has no significant effect on the shape of the polarization curve, indicating that the addition of carbon quantum dot corrosion inhibitors A, B, C, D, and E does not change the reaction mechanism of carbon steel in 1M HCl solution, and it is to prevent the corrosion of carbon steel by occupying the active sites on the surface of carbon steel by adsorption on the surface of carbon steel. At the same time, after adding carbon quantum dot corrosion inhibitors A, B, C, and D, the cathode branch and the anode branch of the polarization curve both move toward the low current density direction, and the movement of corrosion inhibitor E is the largest, which shows that carbon quantum dot corrosion inhibitors A, B, C, and D can simultaneously inhibit the dissolution of carbon steel at the anode and the precipitation of hydrogen at the cathode, and carbon quantum dot corrosion inhibitor D has the best inhibition effect.

[0070] 2. Weight loss experiment and surface morphology analysis of carbon steel in 1M HCl solution at 20°C

[0071] The corrosion rate and inhibition efficiency of carbon steel in 1M HCl without or with 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D were determined by weight loss method at 20°C. The results are shown in Table 3.

[0072] Table 3 Weight loss data of carbon steel at 20℃ immersed in 1M HCl solution for 4h

[0073]

[0074] Table 3 shows that, relative to the blank solution without adding corrosion inhibitor, with the addition of carbon quantum dot corrosion inhibitors A, B, C, and D, the corrosion rate v decreases and the corrosion inhibition efficiency η increases. The corrosion rate of carbon steel in 1M HCl is 1.183 mg·m -2 ·h -1 In 1M HCl solution with 100 mg / L carbon quantum dot corrosion inhibitors A, B, C, and D, the corrosion rates of carbon steel were 0.165, 0.187, 0.160, and 0.133 mg·m, respectively. -2 ·h -1 Among them, corrosion inhibitor D has the lowest corrosion rate and the highest corrosion inhibition efficiency, reaching 88.74%, indicating that carbon quantum dot corrosion inhibitor D is more effective in inhibiting the corrosion of carbon steel in 1M HCl than carbon quantum dot corrosion inhibitors A, B, and C.

[0075] Furthermore, after the experiment, the corrosion morphology of the sample surface was tested using a three-dimensional profilometer, scanning electron microscope and atomic force microscope. The results are as follows: Figure 8 , Fig. 9 , Fig.10 As shown in (3D figure), in each figure (a) is a carbon steel matrix, Figure (b) is without adding corrosion inhibitor, and Figure (c) to Figure (f) are respectively added with 100 mg / L carbon quantum dot corrosion inhibitor A, B, C, D.

[0076] from Figure 8 , Fig. 9 , Fig.10 It can be seen that the surface of the carbon steel without corrosion inhibitor was severely corroded, while the surface of the carbon steel sample with corrosion inhibitor was slightly corroded, indicating that carbon quantum dot corrosion inhibitors A, B, C, and D have a good inhibitory effect on the corrosion of carbon steel in 1M HCl solution, and carbon quantum dot corrosion inhibitor D has the strongest inhibitory effect.

[0077] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing a carbon quantum dot corrosion inhibitor, characterized in that: The following steps are involved: A. After the yellow water from brewing is distilled under reduced pressure and dried, the yellow water organic matter is obtained; B. The yellow water organic matter obtained in step A and water are mixed at a mass volume ratio of 1 g: 1-5 mL, and a hydrothermal reaction is carried out. After the reaction is completed, the mixture is centrifuged, the supernatant is collected for dialysis, and finally freeze-dried to obtain a carbon quantum dot corrosion inhibitor.

2. The method for preparing the carbon quantum dot corrosion inhibitor according to claim 1, characterized in that: In step B, a nitrogen source is also added before the hydrothermal reaction.

3. The method for preparing the carbon quantum dot corrosion inhibitor according to claim 2, characterized in that: In step B, the amount of the nitrogen source added is controlled so that the molar mass ratio of the nitrogen content in the nitrogen source to the organic matter in the yellow water is 0.1-0.5:

100.

4. The method for preparing the carbon quantum dot corrosion inhibitor according to claim 2, characterized in that: In step B, the nitrogen source is at least one of ammonia water, urea, ethylenediamine, triethanolamine or thiourea; preferably, the nitrogen source is triethanolamine.

5. The method for preparing the carbon quantum dot corrosion inhibitor according to any one of claims 1 to 4, characterized in that: In step A, at least one of the following must be met: Before vacuum distillation, filter and remove suspended matter in the yellow wine water. The drying is: low-temperature drying or freeze drying at a temperature not exceeding 50°C.

6. The method for preparing the carbon quantum dot corrosion inhibitor according to any one of claims 1 to 4, characterized in that: In step B, at least one of the following is met: The temperature of the hydrothermal reaction is 180-300°C; The hydrothermal reaction time is 4 to 12 hours; The centrifugal speed is 3000-10000 r / min; The centrifugation time is 20 to 40 minutes.

7. The method for preparing the carbon quantum dot corrosion inhibitor according to any one of claims 1 to 4, characterized in that: In step B, the dialysis is performed using a dialysis bag with a cutoff of 1000 to 3500 Da for 1 to 3 days.

8. Carbon quantum dot corrosion inhibitor, characterized in that: The carbon quantum dot corrosion inhibitor is prepared by the preparation method of the carbon quantum dot corrosion inhibitor according to any one of claims 1 to 7.

9. Use of the carbon quantum dot corrosion inhibitor according to claim 8 in slowing down corrosion of metal substrates in an acidic solution environment.

10. The use according to claim 9, characterized in that: At least one of the following is met: The acidic solution is an aqueous solution of sulfuric acid, hydrochloric acid or nitric acid; The acidic solution H + Concentration is 0.1~6.0mol / L; The added amount of the carbon quantum dot corrosion inhibitor is 5 to 100 mg / L acidic solution.